Perilaku Organizational Citizenship Behavior pada Karyawan - Khairunnisa, Irene; Halida, Arfin Nurma (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Every company is required to be able to improve company performance maximally and effectively, especially to improve individual performance. The low quality of human resources will certainly have a negative impact on the company, while successful companies need employees who are willing to do more than just their formal duties and are willing to provide performance that exceeds expectations. The purpose of this research is to determine organizational citizenship behavior in employees. This research was conducted on 72 permanent employee subjects. The research uses a quantitative approach with saturated sampling techniques. The data collection technique uses a questionnaire with measurements based on organizational citizenship behavior variables. The data analysis technique uses descriptive analysis and determines the calculated average for each aspect. The results of data processing show that the minimum value for the organizational citizenship behavior variable is 82.00 with a maximum value of 134.00 and a mean value of 108.36. The standard deviation value is 10.57809. As for aspects of organizational citizenship behavior, the average obtained was the altruism aspect of 3.15. The average courtesy aspect is 3.31. The average sportsmanship aspect is 3.18. The average conscientiousness aspect is 3.21. The Civic Virtue aspect averages 3.09.